Advances in Cost Economics of Radiation Therapy and Thoracic Surgery for Early-Stage Lung Cancer - Huang, Zhen; Chen, Lulu; Song, Qibin (Zhongliu fangzhi yanjiu, 2025)
The cost economics of early-stage lung cancer treatments is a key focus in the field of lung cancer. The primary treatment modalities for early-stage lung cancer include radiotherapy and thoracic surgery, each offering distinct advantages in therapeutic outcomes and costs. To better understand the cost-effectiveness of radiotherapy versus thoracic surgery for early-stage lung cancer, this paper reviews the progress of recent research on economic evaluations of these two treatment approaches.